2013
DOI: 10.1177/0023677213475438
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the oscillometric technique for intermittent non-invasive arterial blood pressure measurement in the anaesthetized pig

Abstract: This study was designed to evaluate the oscillometric technique for intermittent non-invasive measurement of arterial pressure (AP) in the anaesthetized pig. In six pigs under sevoflurane anaesthesia, intermittent (every 2 minutes) oscillometric measurements of AP made at a forelimb (FL), a hindlimb (HL) and the tail base were compared with simultaneous direct AP measurements made at the aortic arch (AA) over a wide pressure range (30 -140 mmHg of mean AP). All oscillometric measurements strongly correlated (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In a study by Ypsilantis et al., the accuracy of an oscillometric blood pressure device was assessed in inhalant anesthetized pigs. 23 Interestingly, the results obtained in that study showed greater accuracy when the cuff was placed on the thoracic limb. However, the cuff placement on the pelvic limb in that study was proximal to the stifle over the tibia.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In a study by Ypsilantis et al., the accuracy of an oscillometric blood pressure device was assessed in inhalant anesthetized pigs. 23 Interestingly, the results obtained in that study showed greater accuracy when the cuff was placed on the thoracic limb. However, the cuff placement on the pelvic limb in that study was proximal to the stifle over the tibia.…”
Section: Discussionmentioning
confidence: 78%
“…The tail has been shown to provide reliable oscillometric blood pressure readings in awake pigs 30 and a study of anesthetized pigs revealed that the tail provided more accurate readings than the pelvic limb. 23 However, because of the small size of the pigs used in this study, oscillometric measurement of blood pressure via the tail was not possible. Owing to the fact that only one monitor was used, as opposed to several of the same model, and only one cuff design was utilized, it is impossible to conclude with complete confidence that the results obtained in this study would apply to every Waveline Pro monitor and cuff design.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory parameters were adjusted to maintain peripheral blood oxygen saturation (SpO 2 ) ≥ 97% and PaCO 2 = 35-45mmHg. Intraoperative anesthesia was maintained using sevo urane and the appropriate muscle relaxant, cisatracurium besylate (Jianyou Biochemical Pharmaceutical Co., Ltd, Nanjing, China).A warming blanket was used throughout the experiment and body temperature was monitored to maintain the pigs' body temperature at 38-39℃ [15].After preparation, the pigs were placed in the prone position, the forehead was cleaned and the skin was prepared. Following disinfection, a skin incision was made, and a manual skull drill was used to drill until the dura mater was reached.…”
Section: Anesthesia and Monitoringmentioning
confidence: 99%